2013
DOI: 10.1007/s12020-013-0079-8
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance and metabolic syndrome in normal-weight individuals

Abstract: We performed this study to investigate the prevalences of insulin resistance and metabolic syndrome (MetS) in a Chinese population with normal weight. We also examined whether fat mass is associated with insulin resistance and MetS in normal-weight individuals. Data were drawn from a cross-sectional study in China. Subjects with diabetes were excluded. The prevalences of insulin resistance and MetS were calculated. Multivariate logistic regression analysis was performed repeated separately for body mass index … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 20 publications
2
40
0
Order By: Relevance
“…This finding suggests that the presence of tongue WAT inflammation provides clinically relevant information beyond that provided by BMI. Similarly, several recent studies have demonstrated that some phenotypically obese individuals, defined by elevated BMI, are metabolically healthy, whereas metabolic obesity, including insulin resistance, can occur in patients with a normal BMI . Consistent with these observations, we identified tongue WAT inflammation in nearly 20% of individuals with normal or low BMI.…”
Section: Discussionsupporting
confidence: 89%
“…This finding suggests that the presence of tongue WAT inflammation provides clinically relevant information beyond that provided by BMI. Similarly, several recent studies have demonstrated that some phenotypically obese individuals, defined by elevated BMI, are metabolically healthy, whereas metabolic obesity, including insulin resistance, can occur in patients with a normal BMI . Consistent with these observations, we identified tongue WAT inflammation in nearly 20% of individuals with normal or low BMI.…”
Section: Discussionsupporting
confidence: 89%
“…This finding suggests that the presence of breast WAT inflammation may provide clinically relevant information beyond that provided by BMI. It is increasingly recognized that some phenotypically obese individuals, defined by elevated BMI, are metabolically healthy (38-40), while metabolic obesity, including insulin resistance, can occur in others despite a normal BMI (41, 42). Consistent with these observations, breast WAT inflammation occurs in approximately one-third of women with normal BMI (25).…”
Section: Discussionmentioning
confidence: 99%
“…For example, insulin resistance and inflammation have been reported in individuals who have a normal BMI. [17][18][19] Conversely, a minority of individuals with elevated BMI are metabolically healthy. [20][21][22] Accordingly, the current definition of obesity on the basis of BMI has recently been called into question, 23,24 and BMI is inadequate for the identification of patients with adipose inflammation.…”
Section: Introductionmentioning
confidence: 99%